Composting dead swine - James P Murphy; Joseph P Harner (Kansas Agricultural Experiment Station Research Reports, 1998)
Composting dead animals from a swine production facility offers an environmentally sound disposal method to many producers; Swine Day, Manhattan, KS, November 19, 1998
Keywords: Swine day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 819; Swine; Composting; Dead swine